2023
DOI: 10.1097/hco.0000000000001029
|View full text |Cite
|
Sign up to set email alerts
|

Are serum uric acid levels predictors of cardiovascular risk? An update

Abstract: Purpose of reviewThe aim of this review was to update the evidence regarding the link between serum uric acid and cardiovascular risk, as well as the role of nutrition in the prevention and management of hyperuricaemia.Recent findingsThe review focuses on recent epidemiological evidence concerning the role of elevated serum uric acid levels in cardiovascular risk prediction. The dietary prevention and management of hyperuricaemia is also discussed with an emphasis on the adoption of prudent dietary patterns.Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…Though the differences in SBP between the UA groups were not clinically significant. Previous study authors [37,38] reported significant associations between SBP and UA. Hyperuricemia may cause endothelial dysfunction and oxidative stress which can cause reduced blood vessel elasticity and increase stenosis, which can also be associated with elevated levels of SBP.…”
Section: Discussionmentioning
confidence: 81%
“…Though the differences in SBP between the UA groups were not clinically significant. Previous study authors [37,38] reported significant associations between SBP and UA. Hyperuricemia may cause endothelial dysfunction and oxidative stress which can cause reduced blood vessel elasticity and increase stenosis, which can also be associated with elevated levels of SBP.…”
Section: Discussionmentioning
confidence: 81%